Advancing Digital Financial Inclusion in ASEAN : Policy and Regulatory Enablers - World Bank Group (World Bank, Washington, DC, 2019)
This report is intended to support digital financial services (DFS) policymakers in emerging markets and developing economies (EMDEs) and regulators endeavors, by providing a structured approach for the analysis of DFS and financial inclusion. It provides examples of how countries are progressing in pushing further DFS growth, and the type of challenges they are facing. This report could also be a tool for private sector stakeholders when assessing the institutional and regulatory environment to invest in and develop DFS initiatives and provide valuable inputs for their dialogue with the public sector.